DC to AC Converter Frequency Speed Drive Mosfet H-Bridge Topology with Fixed Frequency PWM Sine - Henky Kurnia Dhany; Budhy Setiawan; Sapto Wibowo (International Journal of Frontier Technology and Engineering, 2024)
This paper focuses on simulating a Frequency Speed Drive (FSD) which can regulate frequency changes of 2 to 50 Hz sine wave voltage of 220 Volt RMS. Increasing the frequency of the voltage source provided to the induction motor is expected to increase the rotation speed of the single phase induction motor. This research was carried out by simulating electronic circuits and creating firmware that can regulate the speed of the sine frequency using the PWM (Pulse Width Modulation) Chopping technique with a fixed frequency. Because the PWM Chopping frequency is fixed, the lower the sinusoid frequency the more PWM Chopping will be produced for one wave. Conversely, the higher the frequency of the sinusoid, the less PWM (Pulse Width Modulation) Chopping for one wave will be produced. With this technique, a SPWM wave is produced with a variable frequency and an effective voltage value that is close to a pure sinusoidal wave.